Critical Thinking as a Core Competency in Higher Education - Yusupova , Sitora (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This paper offers an extended exploration of critical thinking as a fundamental competency in higher education. It investigates the role of critical thinking in supporting academic performance, autonomous learning, problem-solving, and informed decision-making, as well as its relevance for preparing students to function effectively in complex professional and social contexts. The study reviews theoretical perspectives, instructional approaches for developing critical thinking, and the challenges associated with its implementation. The results highlight that cultivating critical thinking is essential for intellectual development, adaptability, and lifelong learning in a rapidly evolving knowledge-based society.